Markedly lower follow-up rate after liver biopsy in patients with non-alcoholic fatty liver diseases than those with viral hepatitis in Japan - Hisanaga Yasuhiro; Tanikawa Makoto; Kiriyama Seiki; Kumada Takashi; Toyoda Hidenori; Kanamori Akira; Tada Toshifumi (BMC Research Notes, 2011)
Abstract Background Patients with non-alcoholic fatty liver diseases (NAFLD) are recommended to have periodic follow-up exams because these patients are at increased risk of the presence of non-alcoholic steatohepatitis (NASH), which can lead to cirrhosis or hepatocellular carcinoma. We investigated the follow-up status of NAFLD patients after a liver biopsy examination. Methods We compared the follow-up rates of NAFLD patients who had received an ultrasonography-guided liver biopsy and patients who had received a liver biopsy for chronic viral hepatitis (hepatitis B or C). Results The 1- and 3-year follow-up rates after the liver biopsy were 92.7% and 88.3% for patients with chronic HBV infection, and 93.4% and 88.2% for patients with chronic HCV infection, respectively. In contrast, the follow-up rates for NAFLD patients were 77.6% and 49.9%, respectively, which were significantly lower than those of patients with chronic viral hepatitis (p < 0.0001). Among NAFLD patients, the respective 1- and 3-year follow-up rates were 73.0% and 44.6% for patients with simple steatosis and 80.0% and 52.4% for patients with NASH based on a pathologic diagnosis, without significant difference between these two subgroups (p = 0.5202). Conclusions The outpatient-based follow-up rate after a liver biopsy was significantly lower in NAFLD patients compared to patients with chronic viral hepatitis, regardless of the presence of NASH. It is important to determine how to maintain regular hospital visits for NAFLD patients, preventing patient attrition.